PENGARUH MODEL PEMBELAJARAN DAN TANGGUNG JAWAB TERHADAP HASIL BELAJAR KETERAMPILAN LOMPAT JAUH - Ervan Kastrena, - (2020)
The aim of this study is to examine the effectiveness of the personalized system of instruction (PSI) learning model compared to the direct instruction learning model (DI) as an effort to improve the ability of long jump squat style students. The research method in this study used an experimental method with a 2x2 factorial design. Participants in this study were male students of class X of SMA Negeri 2 Cianjur which numbered 60 students. The instrument in this study was to measure the responsibility of students by using the responsibility questionnaire (Personal Social Respobsibility Quisoner (PSRQ) by Hellison) and for the long jump squat motion test was rating scales. The data analysis technique used ANAVA with SPSS 25. The results revealed that long jump learning with PSI was better than DI, then students with a high level of responsibility reveal that they are more suitable to do learning with PSI while students with a low responsibility attitude experience increased long jump skills through DI. The conclusion is that the PSI learning model can be an effective way to improve squat style long jump skills in high school students in Cianjur.